Design and develop a game for young students to learn essential programming skills: KodeFlo - Lee, Jia Wei (Nanyang Technological University, 2022)
Coding education started 50 years ago with a mechanical tortoise. Developed by the Massachusetts Institute of Technology Artificial Intelligence Laboratory, TORTIS (Toddler's Own Recursive Turtle Interpreter System) is a gadget for young children to learn programming concepts while having fun [1]. Today, block coding is the most used model to teach programming to children and beginners. Scratch is one such example.